Bargaining Power and the Labor Share - a Structural Break Approach - Kornelius Kraft; Alexander Lammers (ZBW - Leibniz Information Centre for Economics, 2021)
In this paper we investigate the relevance of bargaining institutions for the decline of the labor share. Several explanations for the decline exist, which consider the relevance of technology, globalization and markups. Neglected so far is the influence of bargaining institutions, in particular with a focus on changes in the outside option. We provide evidence of this issue, using the Hartz IV labor market reform in Germany as an exogenous shock in the wage bargaining of employees, and investigate its impact on the labor share. We begin by developing a theoretical model in which we outline the effect of a decrease in the outside option within a wage bargaining framework. Thereafter, the approach is twofold. Combining the EU KLEMS and Penn World Table databases, we first endogenously identify the Hartz IV reform as a significant structural break in the German labor share. Second, we estimate the effect of the Hartz IV legislation on the aggregated labor share using a synthetic control approach in which we construct a counterfactual Germany doppelganger. Finally, we use rich firm-level panel data compiled by Bureau van Dijk to support our results on the aggregated labor share. We find that the reform decreases the labor share by 1.6 - 2.7 percentage points depending on method and aggregation level. The synthetic control approach furthermore provides evidence that this effect is persistent over time since the reform.
Keywords: D04; E25; J51; L21; O43; 330; Labor share; Hartz reform; change-point tests; inequality; syntheticcontrol method; GMM